Macro-Microporous Surface with Sulfonic Acid Groups and Micro-Nano Structures of PEEK/Nano Magnesium Silicate Composite Exhibiting Antibacterial Activity and Inducing Cell Responses - Niu Y (Dove Medical Press, 2020)
Yunfei Niu,1 Lieping Guo,2 Fangyong Hu,3 Lishu Ren,4 Qirong Zhou,1 Jiangying Ru,3 Jie Wei4 1Department of Orthopaedics, Changhai Hospital, Second Military Medical University, Shanghai 200433, People’s Republic of China; 2Department of Oncology, Shanghai Eastern Hepatobiliary Surgery Hospital, Shanghai 200438, People’s Republic of China; 3Department of Orthopaedics, The Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou 225009, People’s Republic of China; 4Key Laboratory for Ultrafine Materials of Ministry of Education, East China University of Science and Technology, Shanghai 200237, People’s Republic of ChinaCorrespondence: Yunfei NiuDepartment of Orthopaedics, Changhai Hospital, Second Military Medical University, Shanghai 200433, People’s Republic of ChinaEmail nyunfei1219@163.comJiangying RuDepartment of Orthopaedics, The Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou 225009, People’s Republic of ChinaTel +86-21-311 61690Fax +86-21-31161016Email rujiangying@163.comPurpose: To improve the surface bio-properties of polyetheretherketone (PEEK)/nano magnesium silicate (n-MS) composite (PC).Materials and Methods: The surface of PC was firstly treated by particle impact (PCP) and subsequently modified by concentrated sulfuric acid (PCPS).Results: PCPS surface exhibited not only macropores with sizes of about 150 μm (fabricated by particle impact) but also micropores with sizes of about 2 μm (created by sulfonation of PEEK) on the macroporous walls, and sulfonic acid (-SO3H) groups were introduced on PCPS surface. In addition, many n-MS nanoparticles were exposed on the microporous walls, which formed micro-nano structures. Moreover, the surface roughness and hydrophilicity of PCPS were obviously enhanced as compared with PC and PCP. Moreover, the apatite mineralization of PCPS in simulated body fluid (SBF) was obviously improved as compared with PC. Furthermore, compared with PC and PCP, PCPS exhibited antibacterial performances due to the presence of -SO3H groups. In addition, the responses (eg, adhesion and proliferation as well as differentiation) of bone marrow mesenchymal stem cell of rat to PCPS were significantly promoted as compared with PC and PCP.Conclusion: PCPS with macro-microporous surface containing -SO3H groups and micro-nano structures exhibited antibacterial activity and induced cell responses, which might possess large potential for bone substitute and repair.Keywords: PEEK based composite, sulfonation, macro-microporous surface, antibacterial performances, cell responses